Distance learning of foreign students in the Kazakh and Russian languages (Eurasian Journal of Philology Science and Education, 2022)
The article deals with the problems of distance learning of a language, all types of speech activity: speaking, listening, writing, reading. Methods and techniques of distance learning are analyzed, recommendations are given that help to overcome psychological and linguistic difficulties at teaching two languages in an online format. Attention is focused not only on the linguistic form of the statement, but also on the content. The system of exercises suggested in the article, helps students learn, develops their communication skills and abilities. Common methods and techniques are combined with the capabilities of the online format. The activity of the teacher should be aimed not only at teaching the technique of speaking, listening, writing, reading, but also at a careful selection of literature containing interesting and informative information. Training is a complex and multi-purpose process. The activity of the teacher should be aimed at maximizing the learning process. Taking into account these points allows the teacher to competently organize the audience, adjust the pace, alternative forms of work, which means to activate the activities of students. The communicative principle, which has become the basis of most didactic concepts and has been successfully implemented at almost all stages of education, has significantly strengthened the methodology of communication and linguistics, increased interest in teaching the parameters of the communicative process. The article offers various methodological recommendations that correspond to different stages of training. The article suggests forms of work that will activate the activities of students, their assimilation of Kazakh and Russian languages.